HUBUNGAN POWER OTOT TUNGKAI DENGAN HASIL KECEPATAN TENDANGAN MAWASHI GERI PADA DOJO SDs MARSUDIRINI PERAWANG - Tambunan, Mei Dewi Herianti; Ramadi, Ramadi; Va’i, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem in this study is the mawashi Geri on the Dojo kick technique SDs Marsudirini perawang has not provided satisfactory results on the kick movement speed so as not to give points given. One of the factors in the physical condition that influences the kick speed is strength. Regarding the instruments used in this study the vertical jump test and the Mawashi geri kick test. This study aims to study the relationship of leg muscle strength with the results of the speed of Mawashi Geri's kicks at SD Marsudirini Perawang Dojo. Based on the results of the upper frequency distribution of 6 samples, it turned out that 3 samples (50%) had kick results with a range of values of 14-20 with sufficient categories, then 2 samples (33.33%) had kick results with a value range of 21-23 with good category, starting from 1 sample person (16.66%) has the results starting with various grades 24-26 with excellent categories. From the results of the research described above, it can be concluded that there is something related to leg muscle strength to the speed of mawashi geri kicking in the dojo of SD Marsudirini Perawang, where rtab at a significant level a (0.05) = 0.878 means r count (0.999) (0.878).Key Words: Leg muscle strength, Mawashi kick speed